Предмет: Алгебра,
автор: morgunsergej09
Спростить выраз 2) (6 - m)(6 + m) - m(3 - m).
100 балов дам пж
Ответы
Автор ответа:
1
Ответ:
Объяснение:
(6 - m)(6 + m) - m(3 - m) = 36 + 6m - 6m - m² - 3m + m² = 36 - 3m
Автор ответа:
0
Ответ:
Объяснение:
36-m^2-3m+m^2=36-3m=3(12-m)
nadiyayaremiy12345:
Так це правильно
Похожие вопросы
Предмет: Русский язык,
автор: 5555198
Предмет: Русский язык,
автор: oksana197325
Предмет: Русский язык,
автор: taranalina2016
Предмет: История,
автор: Ano567
Предмет: География,
автор: polinaakaz